Changes in Protein Oxidation, Water-Holding Capacity, and Texture of Bighead Carp (Aristichthys Nobilis) Fillets Under Chilled and Partial Frozen Storage. Issue 5 (28th May 2017) - Lu, Han; Wang, Hang; Luo, Yongkang
ABSTRACT: This study aimed to evaluate the contribution of protein oxidation to the changes in the water-holding capacity (WHC) and texture of bighead carp ( Aristichthys nobilis ) fillets under chilled and partial frozen storage (4°C and −3°C). The results indicated that less protein oxidation occurred to fillets at −3°C than at 4°C, which was reflected by the higher value of salt-soluble protein contents (SSP), total sulfhydryl content (SH), Ca 2+ -ATPase activity, lower water-soluble protein contents (WSP), total disulfide content (SS), and surface hydrophobicity (So-ANS). However, the fillets had better WHC and texture at 4°C, as well as lower drip loss and higher centrifugal loss, hardness, and springiness. A significant linear relationship existed between protein oxidation parameters with WHC and texture characteristics for fillets under both types of storage, but the process of freezing and then thawing, instead of protein oxidation, was the main factor affecting the texture and WHC of fillets at −3°C.